Systematic Review on Effect of Herbal Medicine on Pain after Perineal Episiotomy and Cesarean Cutting - Z Masoumi; A Keramat; R Hajiaghaee (Journal of Medicinal Plants, 2011)
Background: The object of perineal cutting (Episiotomy) is to increase the diameter of outlet pelvic on normal vaginal delivery. This procedure is the commonest surgery cutting in obstetrics the cesarean is the commonest surgery that it s rate incressing in Iran and world. Objective: The object of this systematic review is to summarize the clinical trial performed in Iran and worl. And to survey of safety and efficacy uses of the herbal medicine on pain relief and repair of perineal episiotomy and cesarean cattily. Methods: The searching on information database, SID, Magiran, medline, pubmed, Google schollor, yahoo, Cochrane, tomson, Iran doc is done. The evaluation of article is performed at the basis of jaded scale. First the abstracts of clinical trial performed on herbal medicine in Iran and world are reviewed, then, 18 articles are reviewed at the basis of jaded scale. 12 of them are published in Iranian journal and the other in English journals. Results: The results showed that medicinal herbals are more effective on pain relief and the recovery of perinal episiotomy and cesarean cutting. These can be used after pregnancy but it is necessary to do more study for side effects. Conclusion: Although, in this study, the most herbal medicine has effect on pain and the recovery of perinal episiotomy, but the complicatiore researches are necessary.